The Quality of Justice in Capital Cases: Illinois as a Case Study - Bienen, Leigh B. (Law and contemporary problems, 1998)
Bienen uses Illinois as a case study of injustice in capital cases. The quality of justice in the trial and appeal of capital cases in Illinois is of a very low standard